The Grapevine R2R3-MYB Transcription Factor VvMYBF1 Regulates Flavonol Synthesis in Developing Grape Berries - Czemmel, Stefan (American Society of Plant Biologists, 2009)
Flavonols are important ultraviolet light protectants in many plants and contribute substantially to the quality and health-promoting effects of fruits and derived plant products. To study the regulation of flavonol synthesis in fruit, we isolated and characterized the grapevine (Vitis vinifera ‘Shiraz’) R2R3-MYB transcription factor VvMYBF1. Transient reporter assays established VvMYBF1 to be a specific activator of flavonol synthase1 (VvFLS1) and several other promoters of grapevine and Arabidopsis (Arabidopsis thaliana) genes involved in flavonol synthesis. Expression of VvMYBF1 in the Arabidopsis mutant myb12 resulted in complementation of its flavonol-deficient phenotype and confirmed the function of VvMYBF1 as a transcriptional regulator of flavonol synthesis. Transcript analysis of VvMYBF1 throughout grape berry development revealed its expression during flowering and in skins of ripening berries, which correlates with the accumulation of flavonols and expression of VvFLS1. In addition to its developmental regulation, VvMYBF1 expression was light inducible, implicating VvMYBF1 in the control of VvFLS1 transcription. Sequence analysis of VvMYBF1 and VvFLS1 indicated conserved putative light regulatory units in promoters of both genes from different cultivars. By analysis of the VvMYBF1 amino acid sequence, we identified the previously described SG7 domain and an additional sequence motif conserved in several plant MYB factors. The described motifs have been used to identify MYB transcription factors from other plant species putatively involved in the regulation of flavonol biosynthesis. To our knowledge, this is the first functional characterization of a light-inducible MYB transcription factor controlling flavonol synthesis in fruit.